THE ROLE OF ISLAMIC MICROFINANCE INSTRUMENTS IN POVERTY REDUCTION (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the role of Islamic microfinance instruments in reducing poverty. Since conventional microfinance is largely based on interest (ribа), it may, in some cases, contradict Sharia principles in Muslim societies. Therefore, Islamic microfinance – providing financial services in accordance with Sharia – has gained attention as a sustainable alternative for poverty alleviation. The study primarily focuses on trade-based and partnership contracts, including murаbahah, istiṣnаʿ, mushаrakah, mudаrabah, and tawarruq, and analyzes their application within microcredit models. Evidence from Bangladesh, Nigeria, and Pakistan suggests that Islamic microfinance mechanisms contribute positively to poverty reduction by increasing household income, supporting entrepreneurial activity, and strengthening financial inclusion. The article also highlights practical challenges faced by Islamic microfinance, such as regulatory limitations, insufficient financial literacy, and operational constraints. In the context of Uzbekistan, the effective implementation of Islamic microfinance requires pilot programs, enhanced financial education, improved legal and regulatory frameworks, and the introduction of innovative Sharia-compliant financial instruments.
Keywords: Islamic microfinance; poverty reduction; Sharia-compliant finance; murаbahah; mushаrakah; mudаrabah; istiṣnаʿ; tawarruq; qard hasan; microcredit